Developing Monitoring and Evaluation Frameworks - Markiewicz, Anne and Patrick, Ian (Los Angeles Sage, 2016)
Provides clear, step-by-step guidance on how to develop a monitoring and evaluation framework in a participatory, logical, systematic, and integrated way
Include Appendix, Reference and index
Keywords: Performance standards -- Project management--Evaluation -- Conceptual structures (Information theory)